The effect of varying concentrations of liquid organic fertilizer on the growth and yield of Granola Kembang potato (Solanum tuberosum L.) G0 seed tubers - Kiswara Sandra Gita; Husen Syarif; Iriany Aniek (BIO Web of Conferences)
Farmers typically resort to using seeds obtained from their previous harvests, as the high price of tuber seeds makes them inaccessible. To address this challenge, cultivating quality potato cuttings can be a viable solution. This research aims to evaluate the effect of different concentrations of liquid organic fertilizer on the growth and yield of Granola Kembang potato G0 seed tubers. This study was conducted in Pujon Kidul Village, Malang. The research was carried out from February to June 2023 and involved two stages. In the first stage, four treatments were tested: a control (A0) without the application of LOF, and three treatments with LOF for vegetative phase at concentrations of 1 ml/L (A1), 2 ml/L (A2), and 3 ml/L (A3), each with a dose of 13.88 ml/plant. The second stage involved similar treatments but with LOF for the generative phase. The experiment used a non-factorial completely randomized design (CRD) with four treatments and six replications, resulting in 144 plant samples. The results showed that the application of LOF, particularly at a concentration of 3 ml/L, significantly positively impacted various parameters, such as shoot number, diameter, tuber number, weight, and grading.